2018
DOI: 10.1002/tesq.468
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Does Long‐Term Foreign Language Education Help Improve Spoken Second Language Lexical Proficiency?

Abstract: The current study examined lexical aspects of second language (L2) speech attainment in the foreign language (FL) classroom setting (i.e., several hours of target language input per week). A total of 72 second-year university students with 7 years of FL study and no experience abroad participated in the study. Their spontaneous speech was analyzed via a set of lexical measures and then compared to that of experienced, naturalistic Japanese L2 learners of English. According to the results, their lexical profici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 49 publications
1
18
0
1
Order By: Relevance
“…As for subjective assessment, human rating was adopted as it is widely used to assess spoken lexical proficiency in the area of standardized L2 proficiency testing (e.g. TOEFL, IELTS) as well as L2 speech research (Saito, 2018; Saito, Trofimovich, & Isaacs, 2017; Saito, Webb, Trofimovich, & Isaacs, 2016). Regarding objective assessment, we measured lexical sophistication based on word frequency as an index (Read, 2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for subjective assessment, human rating was adopted as it is widely used to assess spoken lexical proficiency in the area of standardized L2 proficiency testing (e.g. TOEFL, IELTS) as well as L2 speech research (Saito, 2018; Saito, Trofimovich, & Isaacs, 2017; Saito, Webb, Trofimovich, & Isaacs, 2016). Regarding objective assessment, we measured lexical sophistication based on word frequency as an index (Read, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…A picture narrative task was adopted to elicit speech samples. Picture narrative tasks have been extensively used in L2 speech research and found suitable for eliciting and assessing lexical features in spoken texts (Saito, 2018; Saito et al, 2016, 2017; Skehan, 2009) from advanced L2 learners (IELTS 7.0; Li & Lorenzo-Dus, 2014). Comparing the effects of several tasks on lexical use in L2 oral production, Skehan (2009) suggested the utility of narrative task as it can ‘push second language speakers … into using less frequent lexis, presumably as they are responding to the events within the narrative’ (p. 517).…”
Section: Methodsmentioning
confidence: 99%
“…There could still be improvements in vocabulary and morphosyntax at higher proficiency. For example, even advanced L2 learners have been reported to show difficulty acquiring certain lexical features LONGITUDINAL INTERACTION & SLA 4 which are less communicatively important and salient (Saito, 2019), more semantically complex and abstract (Zareva, Schwanenflugel, & Nikolova, 2012), and more infrequent and contextspecific (Kyle & Crossley, 2015). When it comes to the phonological accuracy aspects of language (i.e., pronouncing sounds and words correctly without L1 substitutions), however, any changes are unlikely to happen so rapidly.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Previous research has convincingly shown that different dimensions of L2 learners' vocabulary development take place at different rates. L2 learners quickly acquire lexical features with greater saliency and communicative value, higher frequency or/and more concrete meanings (e.g., Crossley, Salsbury, & McNamara, 2009;Foster & Wigglesworth, 2016;Saito, 2019); few L2 learners can attain nativelike L2 lexical competence, such as abilities to detect conventionalized word combinations (Foster, Bolibaugh, & Kotula, 2014) and access proverbs and idioms (Abrahamsson & Hyltenstam, 2009). To this end, future studies should closely look at the impact of interaction on the multifaceted nature of L2 lexical and morphosyntactic acquisition by using a range of comprehension and production instruments.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation